2006
DOI: 10.1111/j.1574-6968.2005.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Acid phosphatase production byAspergillus nigerN402A in continuous flow culture

Abstract: The production of acid phosphatases (E.C.3.1.3.2, ACPs) by Aspergillus niger N402A is regulated by specific growth rate, as well as phosphate availability and pH, as demonstrated by studies in continuous flow culture. Specific ACP activity was highest when A. niger was grown at pH 6.3 (64+/-8 U g(-1)) or pH 2.8 (99+/-11 U g(-1)), at a dilution rate of 0.07 h(-1) and phosphate concentrations below 0.46 mM. ACP production was growth correlated for specific growth rates between 0.07 and 0.13 h(-1). Four different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…The effect of phosphate concentration in the culture medium on phosphatase activity has been previously reported in fungi (Kang et al ., ; Ogbo, ; Rinu & Pandey, ). Acid phosphatase activity is under the control of a regulatory mechanism of repression and derepression and is regulated by the concentration of phosphate (Hidayat et al ., ). In our study, we observed that this regulatory mechanism has a greater impact on B. cepacia than A. niger or a co‐culture.…”
Section: Discussionmentioning
confidence: 97%
“…The effect of phosphate concentration in the culture medium on phosphatase activity has been previously reported in fungi (Kang et al ., ; Ogbo, ; Rinu & Pandey, ). Acid phosphatase activity is under the control of a regulatory mechanism of repression and derepression and is regulated by the concentration of phosphate (Hidayat et al ., ). In our study, we observed that this regulatory mechanism has a greater impact on B. cepacia than A. niger or a co‐culture.…”
Section: Discussionmentioning
confidence: 97%
“…These taxa might therefore contribute to production of these two enzymes. Previous studies have shown that A. niger can produce high amounts of both acid phosphatase and β-glucosidase [48,49]. Furthermore, Penicillium citrinum can reportedly produce high amounts of β-glucosidase [50].…”
Section: Potential Soil Microbial Ecological Functionsmentioning
confidence: 99%
“…The results clearly demonstrated that A. niger contained an intra and extracellular acid phosphatase, but not an alkaline phosphatase (data not included). The effect of the Pi concentration on the growth and phosphatase activity have been shown on A. niger (Gargova and Sariyska 2003;Hidayat et al 2006). Various fungi exhibit both intracellular and extracellular APases; for example, A. fumigatus (Bernard et al 2002) and A. niger, A. awamori, Emmericella nidulans, E. rugulosa, Penicillium simplicissimum and P. rubrum (Yadav and Tarafdar 2003).…”
Section: Effect Of Inorganic Phosphate (Pi)mentioning
confidence: 99%
“…Several hydrolytic enzymes play a major role in the mineralization processes of organic P substrates (Annaheim et al 2010). Organic compounds, which appear as phosphate esters, are hydrolysed by phosphatases to produce phosphate, which can then be assimilated by the plants (Hidayat et al 2006;Nannipieri et al 2011). These enzymes are secreted by the plants and microorganisms when the content of soluble phosphate in the soil is low (Samuel et al 2010).…”
Section: Introductionmentioning
confidence: 99%